Implementasi Virtual Private Server untuk Mini Hosting - Carlin Gea; Kristian Juri Damai Lase; Mariana Syamsudin (Infact: International Journal of Computers, 2023)
Virtual Private Server is a private server whose entire resource is used by one user only and is not influenced by other users. The technology used by VPS is virtualization of physical server hardware which is then divided into several different resources. Called virtual because this division uses software so that in one physical server there are several VPS running. To be more extensive in terms of server control, researchers use Public IP and Dedicated IP as a distributor of VPS systems from local to public. In addition, in this VPS implementation, debian linux and ubuntu linux are used as operating systems to create a VPS server. To get the value of the VPS network performance test from the client using the parameters of the Quality of Service (QoS), namely Delay and Jitter. From the test results, the value of the VPS server resource obtained can be categorized as very good and feasible to be implemented with an average server CPU load of 2.9%, memory 71.23%, disk space 16.1%. And testing the QoS parameters (delay, jitter) also gets good performance and has a fairly low value obtained with an average delay value of 6-37.24%, jitter of 8.95-59.95%.